In vitro evaluation of the effects of Ultrasound Tongue Scraper on bacteria and biofilm formation. Issue 4 (21st September 2019) - Amaechi, Bennett T.; Abdul Azees, Parveez Ahamed; Menon, Suchitra; Kasundra, Hariyali
Abstract: Aim: Oral malodor is a common condition caused by some Gram‐negative oral bacteria, among which are the 3 red complex bacteria (RCB). The present study investigated the effectiveness of the Ultrasound Tongue Scraper (UTS) to disrupt the structural morphology of the bacteria and their biofilm. Methods: While developing over 72 hours, multispecies biofilms of RCB ( Porphromonas gingivalis, Tryponema denticola, Tannerella forsythia ) were treated every 24 hours with 1.6‐MHz ultrasound waves generated with UTS. An untreated group served as controls. Confocal laser scanning microscopy was used to determine the biofilm thickness, biomass and live : dead cell ratio at each time point (24, 48 and 72 hours). Biofilm morphology and bacteria ultrastructure were viewed using scanning/transmission electron microscopy, respectively. Data were analyzed using ANOVA and Tukey tests. Results: At each time point, the 3 variables were significantly lower in treated samples than the untreated. Significant biofilm disruption was observed in treated samples at each time period while the untreated had intact biofilm morphology. Cells in treated samples showed disrupted cell wall, cytoplasmic material, huge vacuoles and heterogeneity in electron density, while these cell organelles remained intact in untreated samples. Conclusion: The UTS has an inhibitory effect on RCB and could be useful for oral malodor management.